PENGGUNAAN MEDIA BONEKA TANGAN DALAM PENERAPAN HAFALAN HADITS - Nurazizah, Indah; Suprihatin, Suprihatin; Tirtajaya, Mas Deden; Wastoni, Oni (LPPM Universitas Islam 45, 2024)
Islamic religious education is an effort and method designed to help educators and students consistently understand correct moral knowledge. Apart from the scientific aspect, Islamic religious education is also considered a guide to human life. The results of problem analysis through observations and interviews regarding community service activities in Ridomanah Village, found that there was no teaching about Hadith. The community service program in this activity is about implementing Hadith memorization for TPQ children in Ridomanah Village with learning media in the form of hand puppets using a short story line method entitled